Bridge pile foundation drilling slag utilization method

By separating and treating drilling slag, using mud and curing slag materials, the problem of high slag treatment cost in drilling construction is solved, and resource conservation and production efficiency are improved.

CN119641270APending Publication Date: 2025-03-18SINOHYDRO BUREAU 5
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916192.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The yield of slag and mud produced during drilling construction is large, and the transportation and consumption costs are high, which affects production efficiency.

Method used

By separating the drilling slag, slurry and slag are sieved out, the slurry is used to continue to be used for drilling, and the slag is added (such as cement, fly ash and polymer solution) is added to treat the slag, forming a solidified substance for filling.

Benefits of technology

It reduces the transportation and consumption costs of slag materials, saves resources, improves production efficiency, and improves the strength of slag materials through curing treatment to meet the filling requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119641270A_ABST
    Figure CN119641270A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of drilling construction, and particularly discloses a bridge pile foundation drilling slag utilization method which comprises the following steps: S1, separating slag to screen out slurry and slag; s2, the slurry separated in the step S1 is used for bridge pile foundation drilling; s3, adding a curing material into the residue soil material separated in the step S1 to form a cured material; the curing material comprises a curing agent and a polymer solution; and S4, filling the cured material formed in the step S3 in the area to be filled. The slag generated in the drilling construction process is recycled, so that the transportation and consumption cost of the slag can be greatly reduced, resources are saved, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling construction, and in particular to a method for utilizing drilling slag for a bridge pile foundation. Background Art

[0002] The bridge pile foundation is the lowest part of the bridge structure that is in direct contact with the foundation and is an important part of the bridge substructure. The bridge pile foundation requires bored cast-in-place piles, which are piles made by forming pile holes in the foundation soil at the construction site through mechanical drilling, steel pipe squeezing or manual excavation, placing steel cages in them, and pouring concrete.

[0003] During the drilling construction process, a large amount of debris and mud will be generated. If not properly handled, the debris and mud will cause environmental pollution. The relevant debris and mud treatment technology is to transport the debris and mud to a fixed disposal site for solidification and disposal to avoid impact on the environment.

[0004] At present, due to the large amount of slag and mud produced during drilling construction, the transportation and disposal costs are high, and it affects production efficiency. Summary of the invention

[0005] The purpose of the present invention is to utilize the slag generated during the drilling construction process, thereby greatly reducing the transportation and disposal costs of the slag, saving resources, and improving production efficiency.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: A method for utilizing bored slag of a bridge pile foundation comprises the following steps: Step S1: separating the slag material to screen out mud and slag material; Step S2: using the mud separated in step S1 for drilling bridge pile foundations; Step S3: adding a solidifying material to the slag material separated in step S1 to form a solidified product; the solidifying material includes a curing agent and a polymer solution; Step S4: Fill the solidified material formed in step S3 in the area to be filled.

[0007] Preferably, the curing agent includes cement, and the mass percentage of cement in the slag material is 10% to 14%.

[0008] Preferably, the curing agent also includes fly ash, and the ratio of cement to fly ash is 8:3.

[0009] Preferably, the polymer solution comprises polyacrylamide and sodium polyacrylate, wherein the ratio of the polyacrylamide to the sodium polyacrylate is 1:1 to 4:1.

[0010] Preferably, the concentration of the polyacrylamide is 60 μM to 70 μM, and the concentration of the sodium polyacrylate is 30 μM to 40 μM.

[0011] Furthermore, the step of adding solidifying material to the slag material to form a solidified product in step S3 includes: Step S31: transporting the separated soil material to a mixing tank; Step S32: Calculate the dosage of the solidifying material according to the size of the stirring tank; Step S33: pour the solidifying material into the stirring tank, and stir it in different zones in the stirring tank to form a solidified material.

[0012] Furthermore, the step of filling the solidified material in the area to be filled in step S4 includes: S41: filling and spreading the solidified material in the area to be filled to form a filling layer; S42: The filling layer is leveled and compacted until the filling layer begins to set, thus completing the filling.

[0013] Preferably, the filling layer has a thickness of 30 cm to 50 cm.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. Separate the slag produced by drilling into mud and slag. After the mud is treated, it is transported back to the mud pool for continued use. After the slag is solidified, it is used for filling to reduce the disposal cost.

[0015] 2. The curing agent is cement, and the mass percentage of cement in the slag material is 10% to 14%. When the mass percentage of cement in the slag material reaches 11%, the strength of the slag material can reach 250kpa. Considering the cost, the mass percentage of cement in the slag material can be 11% to 14%. Within this range, the strength of the slag material can be greater than 250kpa.

[0016] 3. The curing agent also includes fly ash, and the ratio of cement to fly ash is 8:3. Under the ratio of 8% cement + 3% fly ash, the obtained mud solid can not only be effectively processed, but also meet the needs of on-site temporary construction (strength can be greater than 250kpa), reducing construction costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of the present invention.

[0018] Figure 2 It is a schematic diagram of the screening process of the present invention.

[0019] Figure 3 for Figure 2 Schematic diagram of the principle of mud separation equipment.

[0020] Figure 4 This is the unconfined compressive strength variation curve with different amounts of quicklime.

[0021] Figure 5 This is the variation curve of unconfined compressive strength of cement with different dosages.

[0022] Figure numerals: 11 - slurry inlet pipe, 12 - pre-screen, 13 - slurry storage tank, 14 - slurry pump, 15 - desander, 16 - fine screen, 17 - intermediate storage tank, 10 - mud separation equipment, 20 - drilling rig, 30 - borehole, 40 - primary sedimentation tank, 50 - mud tank. DETAILED DESCRIPTION

[0023] The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention, so as to have a further understanding of the concept of the present invention, the technical problems solved, the technical features constituting the technical scheme and the technical effects brought about.

[0024] like Figure 1 As shown, a method for utilizing bored slag of a bridge pile foundation comprises the following steps: Step S1: Separate the slag material to screen out mud and slag material; in the process of forming the bored pile 30, the main functions of the mud are to clean the bottom of the hole, suspend the slag material, balance the bottom pressure and water pressure inside and outside the hole, protect the hole wall from collapse, cool the drill and other purposes. During the construction of the drilling hole 30, a large amount of mud will flow out, and the drilling hole 30 will produce a large amount of slag material. The slag material and the mud will be mixed together to form slag material, that is, the slag material is a mixture of mud and slag material, wherein the slag material mainly includes crushed stone, soil sand and other materials. The slag material can be separated by the mud separation device 10 to screen out the mud and slag material; wherein the moisture content of the slag material is less than 20%.

[0025] The drilling rig 20 is constructed to form a borehole 30. In actual operation, the drilling rig 20 can cooperate to send the separated mud into the primary sedimentation tank 40 through a pipeline, and then the mud extraction system can send the mud to be treated into the mud separation equipment 10 through a pipeline, and the treated mud is transported to the mud pool.

[0026] During the drilling operation, there are requirements for the quality of the mud. The quality of the mud will directly affect the pile quality and drilling speed of the bored pile. Therefore, the preparation of the mud is a very important link in the pile construction of the bored pile.

[0027] In view of the working conditions that the construction area is mostly composed of silty clay layers, silt layers, and silty clay layers, the on-site pile foundation is a large-diameter extra-long pile. If the traditional domestic mud natural circulation process is adopted, there will be problems such as large processing flow, large site occupation, low mud processing quality and slow speed, and difficulty in mud quality control, which will affect the quality of the pile foundation. At the same time, there are also large mud losses and high costs for treating waste mud in accordance with environmental protection requirements. By comparing the existing mud treatment technologies and considering factors such as equipment cost, efficiency, and maintenance, the YG-250 mud separation equipment 10 can be selected.

[0028] YG-250 mud separation equipment 10 is mainly suitable for large-diameter pile foundation projects and anti-seepage wall projects that adopt mud wall protection and circulation drilling technology. Its technical performance is as follows: maximum mud processing capacity 250m³ / h: purification and sand removal efficiency is more than 90%; the slag screening capacity can be adjusted according to the different footage of the hole-making machine, and the moisture content of the screened slag material is less than 20%, so that the subsequent solidification effect is better; the maximum specific gravity of the treated slurry is less than 1.2, the viscosity is less than 40s, and the sand content is less than 20%; the total installed power is 58.6kW; the equipment dimensions (length, width, height) are 3.5m×2m×2.5m; the whole machine weight is 3.6t.

[0029] The slurry sucked out from the bottom of the hole by the reverse circulation gravel pump is transported to the pre-screen 12 of the mud treatment system through the main slurry inlet pipe 11. The slag material with a particle size of more than 5 mm is separated through its vibration screening. The mud that passes through the first screen enters the slurry storage tank 13 of the desander at the same time, and the slurry pump 14 of the desander sucks the mud from the tank. The mud with a certain amount of energy stored at the outlet of the pump is injected tangentially from the slurry inlet of the hydrocyclone along the slurry hose. After the hydrocyclone is sorted, the mud with fine particle size is discharged from the sand settling at the lower end of the cyclone and falls into the fine screen 16. After dehydration and screening by the fine screen 16, the drier fine slag material is separated. The mud that passes the second screening is circulated back to the slurry storage tank 13. The treated clean mud enters the middle storage tank 17 from the cyclone overflow pipe, and then is transported back to the hole along the main slurry outlet pipe.

[0030] A branch controlled by a backflush valve is installed at the outlet of the slurry pump 14 of the desander and communicated with the slurry storage tank 13. By opening the backflush valve, the precipitated slag material in the slurry storage tank 13 can be disturbed so that the slurry storage tank 13 will not cause siltation and sedimentation due to long-term use.

[0031] During the mud circulation process, a control float between the middle tank 17 and the slurry storage tank 13 keeps the liquid level in the desander slurry storage tank 13 constant. Once the amount of slurry output from the slurry storage tank 13 is greater than the amount of slurry supplied, the float will fall as the liquid level drops, and the slurry in the middle tank 17 will be transferred to the slurry storage tank 13 through the opened slurry supply pipe, so the liquid level rises until it returns to its original state, and the control float also rises and seals the slurry supply pipe of the middle tank 17. At this time, if the amount of slurry supplied is greater than the amount of slurry output, the overflow pipe of the slurry storage tank 13 will overflow to prevent slurry overflow. When higher quality mud is required, the purpose can be achieved by reducing the total amount of slurry fed and repeating the mud separation process of the hydrocyclone.

[0032] Step S2: Use the mud separated in step S1 for bridge pile foundation drilling 30; since the mud separation equipment 10 screens the slag material from the mud, the mud entering the mud pool can be normally used for the drilling 30 of the cast-in-place pile and the hole cleaning process, thereby realizing the recycling of the mud, thereby saving mud resources, reducing the amount of mud preparation, and reducing the cost of processing waste mud. Of course, part of the mud can be recycled and purified according to actual needs.

[0033] Of course, in order to ensure that the mud after purification can meet the requirements of the construction specifications for mud, the mud needs to be tested. Specifically, during the drilling process 30, the on-site construction site laboratory tests the mud technical parameters at the beginning and during the mud mixing process. The process control is to test once every 100m³ of mixing, and to sample the mud at the mud inlet of the drilling rig 20 at a frequency of once every 2 hours. The main test data include the specific gravity, viscosity, sand content, pH value, etc. of the mud as a judgment of the difference between the mud after the mud circulation treatment system and the initial mud and whether it meets the requirements of the construction specifications for mud.

[0034] Step S3: Add solidifying materials to the slag separated in step S1 to form a solidified material; the sieved slag can be used for temporary construction projects such as road filling to reduce the cost of purchasing slag and the cost of handling slag. According to the on-site construction needs, considering the transportation needs of large vehicles such as prefabricated T-beams, cranes, and concrete tankers involved in the construction of the road, the foundation bearing capacity of the construction road and some temporary filling areas should not be less than 250kPa, that is, the strength of the slag should be greater than 250kPa to meet the filling requirements. However, since the sieved slag has a high water content and its strength does not meet the filling requirements, it is necessary to add suitable solidifying materials to the slag so that the solidified slag can meet the filling requirements.

[0035] The solidifying material includes a solidifying agent and a polymer solution, and the polymer solution is used to improve the subsequent mud cake formation of the slag material.

[0036] It should be noted that the order of step S2 and step S3 is not limited. Step S2 may be executed first and then step S3, step S3 may be executed first and then step S2, or step S2 and step S3 may be executed simultaneously. Of course, step S4 is executed after step S3.

[0037] Step S4: Fill the solidified material formed in step S3 in the area to be filled.

[0038] Preferably, the curing agent includes cement, and the mass percentage of cement in the slag material is 10% to 14%.

[0039] Regarding the selection of curing agent, considering the on-site construction conditions, a large number of curing studies were conducted using existing resources, and it was found that the curing materials that can be used for slag materials are cement, quicklime and fly ash. The curing principles of cement, quicklime and fly ash are: 1) Lime solidification material: Lime is used as a solidification material. After being added to the mud, it has a strong chemical and physical reaction with the soil, which fundamentally changes the physical and mechanical properties of the soil. The stabilizing effect of lime solidification material is manifested in the reduction of soil plasticity, and in the later stage, it is manifested in the improvement of soil strength and stability; 2) Cement solidification materials: Cement is added to the mud, and with the participation of water, the cement undergoes hydrolysis and hydration reactions to produce cement hydrates. These cement hydrates will produce physical and chemical reactions with clay particles to form a cement stone skeleton with good integrity, high stability and certain strength; 3) Fly ash solidifying material: The solidifying effect of fly ash is that the solidifying material and the molecules of the solidified object adsorb each other to produce cohesion, thus forming a certain solidifying effect.

[0040] After determining the solidification material, in order to better determine which solidification material has a better and more economical solidification effect, it is necessary to conduct an unconfined compressive strength test of the mud solidification material, and determine the main solidification material based on this. The specific steps are: 1. Determine the quantitative value of the curing test: During the experiment, eight groups of control tests were set up, each of which contained a 2KG mud taken from the same mud pool as the basic material; 2. Determine the variables of the solidification test: In the mud solidification test, the type of solidification material and the amount of solidification material are used as variables for control; 3. Selection of the type of mud solidification material: According to the solidification mechanism of the solidification material, the solidification material is selected with lime solidification material and cement solidification material with strong solidification ability for testing; 4. Determination of the amount of solidifying material added: The amount of solidifying material added is designed based on the wet weight of the mud (addition amount = mass of solidifying material added / wet weight of the mud). During the research process, quicklime and cement with different contents (e.g. 7%, 9%, 11%, 14%) were added to the mud, and after being fully stirred in a mixer, a standard curing period of 1 day was carried out (temperature 20 degrees Celsius, humidity 98%). 5. Preparation and testing of cured product samples: After the cured product is initially formed, standard test samples are prepared. Three parallel tests are conducted for each group of tests. After the sample preparation is completed, the compressive strength test is carried out using a compression testing machine after standard curing for 7, 14, and 28 days.

[0041] like Figure 4 , Figure 5 As shown in the figure, during the research process, unconfined compressive strength tests were carried out on mud solidified with different amounts of quicklime and cement alone, and the unconfined compressive strength of mud solidified with quicklime alone and cement alone with the increase of age was obtained. Among them, when quicklime alone was added, the strength growth in the early stage was relatively slow, and the strength growth in the later stage was relatively fast, while the early strength increase of cement solidified mud was greater than the later strength growth. Compared with the strength of quicklime alone, the unconfined compressive strength of cement alone is much higher, indicating that cement has a better solidification effect on slag materials than quicklime. Therefore, cement is selected as the main solidification component of the solidifying agent. Figure 4 and Figure 5 It can be seen that when the mass percentage of cement in the slag material reaches 11%, the strength of the slag material can reach 250kpa. For cost considerations, the mass percentage of cement in the slag material can be 11%~14%. Within this range, the strength of the slag material can be greater than 250kpa.

[0042] By analyzing the solidified material treated with cement solidifying materials, it is found that when the cement content reaches 11%, the 28-day unconfined compressive strength of the mud solidified material is 297kPa. Considering the economy in the construction process, reducing construction costs, and making full use of the solidifying material mechanism, fly ash can be used to replace part of the cement as the mud solidifying material, that is, the solidifying material can include cement and fly ash.

[0043]

[0044] Preferably, the curing agent also includes fly ash, and the ratio of cement to fly ash is 8:3. Table 1 lists the 28-day unconfined compressive strength of mud solids at different curing agent dosages. It can be seen from Table 1 that at the ratio of 8% cement + 3% fly ash, the obtained mud solids can not only be effectively treated, but also meet the needs of on-site temporary construction (strength can be greater than 250kpa), reducing construction costs. Therefore, the ratio of cement to fly ash can be: 8:3. Among them, the mass percentage of cement to slag material can be 8%, and the mass percentage of fly ash to slag material can be 3%.

[0045] Preferably, the polymer solution comprises polyacrylamide and sodium polyacrylate, wherein the ratio of the polyacrylamide to the sodium polyacrylate is 1:1 to 4:1.

[0046] Regarding the selection of polymer solution. Through a large number of experiments, it was found that adding aqueous solutions of chemical materials, such as polyacrylamide, sodium carboxymethyl cellulose, vegetable gum, xanthan gum, water reducer, guar gum, etc., can improve the subsequent mud cake formation of slag materials. The polymer solution can include polyacrylamide and sodium polyacrylate, wherein the ratio of polyacrylamide to sodium polyacrylate is: 1:1~4:1.

[0047] By utilizing the network structure of low-concentration polyacrylamide aqueous solution, the slag particles are aggregated together through physical, mechanical and chemical effects between the slag particles, and most of the water in the slag exists in the slag in the form of weakly bound water. Due to the network structure of low-concentration polyacrylamide aqueous solution, water outside the slag is not easy to invade the slag, the slag will not be diluted, and will not cause gushing. The water inside the slag is not easy to lose, and the water loss under pressure is small, and it will not cause mud cakes. Low-concentration sodium polyacrylic acid aqueous solution forms an adsorption layer on the surface of the slag particles, which increases the charge on the surface of the particles and increases the repulsive force between the particles that form a three-dimensional barrier. At the same time, a double electric layer structure is formed on the surface of the slag particles, which increases the thickness of the double electric layer. The particles are separated by electrostatic repulsion, and have good dispersion performance between the slag particles. The particles are not easy to stick together, which can reduce the probability of mud cakes in the slag. Low-concentration polyacrylamide aqueous solution and low-molecular-weight and low-concentration sodium polyacrylic acid aqueous solution can make the slag system uniform, increase the suspension performance, and make the slag not stratified, and the slag in the soil compartment uniform.

[0048] Preferably, the concentration of the polyacrylamide is 60 μM to 70 μM, and the concentration of the sodium polyacrylate is 30 μM to 40 μM.

[0049] Furthermore, the step of adding solidifying material to the slag material to form a solidified product in step S3 includes: Step S31: transport the separated slag material to the mixing tank. For the section in the construction area where the access road or regional backfill is required, a mixing tank is selected nearby to provide a bearing site for mechanical mixing according to the actual engineering situation, and a movable cement tank and fly ash tank are set near the mud tank 50.

[0050] Step S32: Calculate the amount of the solidifying material according to the size of the mixing tank. Since the proportion of the solidifying material and the density of the solidifying material and the slag material are known, the amount of the solidifying material can be calculated according to the volume size of the mixing tank.

[0051] Step S33: pour the solidified material into the mixing tank and stir it in different areas in the mixing tank to form a solidified product. On-site mixing can be carried out by using a mixing head on the on-site excavator to stir the on-site materials, and the mixing can be carried out in different areas to make the mixing more uniform, until the slag material and the solidified material are completely mixed to form a solidified product that meets the filling requirements.

[0052] Furthermore, the step of filling the solidified material in the area to be filled in step S4 includes: S41: Spread the solidified material in the area to be filled to form a filling layer. After the mixing is completed, the slurry solidified material is dug out from the slurry pool 50 by using an excavator and a dump truck and transported to the roadbed or filling area to be filled. The filling thickness is generally 30cm to 50cm. When using a dump truck to unload, attention should be paid to the unloading distance.

[0053] S42: The filling layer is leveled and compacted until the filling layer is initially set, and the filling is completed. A bulldozer can be used to lay the material on the roadbed according to the thickness of the material, and a leveler can be used to level and compact it before the solidified material is initially set. After the leveling is completed, moisturizing and curing should be carried out in time. The curing is carried out by sprinkling water. The curing period is 7 days. Before the curing is completed, the construction volume should be avoided to prevent damage to the road surface.

[0054] Preferably, the filling layer has a thickness of 30 cm to 50 cm.

[0055] In summary, the embodiment of the present application provides a method for utilizing the drilling slag of a bridge pile foundation, which can fully purify the mud and meet the quality control requirements of pile construction. The full purification of the mud and the effective separation of soil slag, sand and stone are conducive to improving the efficiency of hole making, controlling the mud index, and having a significant effect on cleaning the hole and reducing the stuck hole, and saving the mud cost. At the same time, the slag material produced can be used in temporary construction projects such as road filling, reducing the cost of purchasing slag materials. In addition, since the mud and slag materials can be recycled, the transportation and disposal costs of the mud and slag materials are greatly reduced, the transportation time is reduced, and the production efficiency is improved. Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for utilizing bored slag from bridge pile foundation, characterized in that: The following steps are involved: Step S1: separating the slag material to screen out mud and slag material; Step S2: using the mud separated in step S1 for drilling bridge pile foundations; Step S3: adding a solidifying material to the slag material separated in step S1 to form a solidified product; the solidifying material includes a curing agent and a polymer solution; Step S4: Fill the solidified material formed in step S3 in the area to be filled.

2. A method for utilizing bored slag from bridge pile foundation according to claim 1, characterized in that: The curing agent includes cement, and the mass percentage of cement in the slag material is 10% to 14%.

3. A method for utilizing bored slag from bridge pile foundation according to claim 2, characterized in that: The curing agent also includes fly ash, and the ratio of cement to fly ash is 8:

3.

4. The method for utilizing bored slag of a bridge pile foundation according to claim 1, characterized in that: The polymer solution includes polyacrylamide and sodium polyacrylate, wherein the ratio of the polyacrylamide to the sodium polyacrylate is 1:1 to 4:

1.

5. A method for utilizing bored slag from bridge pile foundation according to claim 4, characterized in that: The concentration of the polyacrylamide is 60 μM to 70 μM, and the concentration of the polyacrylic acid sodium is 30 μM to 40 μM.

6. The method for utilizing bored slag of bridge pile foundation according to claim 1, characterized in that: The step of adding solidifying material to the soil material to form a solidified product in step S3 includes: Step S31: transporting the separated soil material to a mixing tank; Step S32: Calculate the dosage of the solidifying material according to the size of the stirring tank; Step S33: pour the solidifying material into the stirring tank, and stir it in different zones in the stirring tank to form a solidified material.

7. The method for utilizing bored slag of bridge pile foundation according to claim 1, characterized in that: The step of filling the solidified material in the area to be filled in step S4 comprises: Step S41: filling and spreading the solidified material in the area to be filled to form a filling layer; Step S42: Level and compact the filling layer until the filling layer is initially solidified, thus completing the filling.

8. The method for utilizing bored slag of bridge pile foundation according to claim 7, characterized in that: The thickness of the filling layer is 30 cm to 50 cm.